Reporting rates for severe hypersensitivity reactions associated with prescription‐only drugs in outpatient treatment in Germany. (19th August 2015) - Sachs, Bernhardt; Fischer‐Barth, Wilma; Merk, Hans Friedrich
Abstract Purpose To determine which 10 prescription‐only drugs used in outpatient treatment in Germany are most frequently reported to induce severe drug hypersensitivity reactions taking into account their prescription numbers. In addition, the reader should be made aware of respective databases available to the public and their limitations. Methods Reports of anaphylactic and severe cutaneous adverse reactions were identified in the adverse drug reaction database of the German competent authority for the time period January 1998 to December 2012. For frequently reported drugs, the total number of reports was matched with their total number of prescriptions resulting in the reporting rate. Results Among the 10 drugs with the highest reporting rate for anaphylactic reactions, there were six antibiotics (moxifloxacin, levofloxacin, clindamycin, ciprofloxacin, cefuroxime and amoxicillin), three of which were fluoroquinolones. The other four drugs were glatiramer, metamizole and two angiotensin‐converting‐enzyme inhibitors. Concerning severe cutaneous adverse reactions, four out of ten drugs were antibiotics (clindamycin, sulfamethoxazol + trimethoprim, ciprofloxacin and amoxicillin), and three were anticonvulsives. Because dental prescription numbers were not available to the public, the real reporting rates for clindamycin and to a lesser extent for amoxicillin are presumably lower. Conclusions The predominance of antibiotics among the reports of severe immediate and delayed‐type drug hypersensitivity reactions is largely in accordance with literature although fluoroquinolones seem to be slightly overrepresented concerning anaphylactic reactions. The reader should be aware of the limitations of adverse drug reaction and prescription databases available to the public, and that over‐the‐counter drugs, such as non‐steroidal anti‐inflammatory drugs, and drugs typically administered in hospitals could not be considered. Copyright © 2015 John Wiley & Sons, Ltd.